Eskimofrau in Tracht : [19--] - Hettasch, Paul, 1873-1949. (2001)
Black and white photograph of an Inuit woman wearing a winter outfit made of seal skin and fur. Black and white photograph of an Inuit woman wearing a winter outfit made of seal skin and fur.